Israeli Practices against the Primary Schools in the Eastern Part of the City of Islamicjerusalem (2000-2016) - Awawda, Sabreen; Yatiban, Aminurraasyid; El-Awaisi, Abd Al-Fattah (Online Journal of Research in Islamic Studies, 2019)
The study aims to identify the Israeli measures against primary schools in East Islamicjerusalem. To do so, this research reviewed references about Israeli government policies on the primary education system in the eastern part of the city of Islamicjerusalem, obtained statistics from a 78 validate survey out of 80, which were distributed to different schools’ staff. The methodology of statistical analysis was used through means and standard deviations and one sample t-test. T Findings of the study revealed that Israel’s actions have a negative effect on the development of the primary schools process in East Islamicjerusalem. Based on the findings the author recommended Palestinian Ministry of Education of both the strengthen students and teachers resilience in Arab schools in the eastern part of the city of Islamicjerusalem; in addition to, the need to find a plan to protect students, teachers and primary schools in the eastern part of the city of Islamicjerusalem. The author also recommended Schools management to work on promoting the Palestinian national identity and support the education of Palestinian culture, and to introduce students to the Palestinian issue (of national identity) verbally without relying on the curriculum. Moreover, the author recommended that Palestinian people in the eastern part of the city of Islamicjerusalem must continue to fight for their rights to education with the Israel occupation. Finally, she recommended the Palestinian National Authority to provide adequate financial support to educational institutions in the eastern part of the city of Islamicjerusalem.